# Pre-Calculus

posted by .

For the function
f(x)=3x^3−42x

Compute the difference quotient
[f(x+h)−f(x)]/h,h≠0

I checked my work like 3 times and still got [(-2x^3)+(3hx^2)+(3xh^2)+(h^3)-(42h)]/h

Is it wrong?

• Pre-Calculus -

looks like you forgot that pesky 3 out front.

f(x+h) = 3(x+h)^3 - 42(x+h)
= 3x^3 + 9x^2h + 9xh^2 + 3h^3 - 42x - 42h
f(x) = 3x^3 - 42x
subtract to get

9x^2h + 9xh^2 + 3h^3 - 42h

now divide by h to get

9x^2 + 9xh + 3h^2 - 42

## Similar Questions

1. ### Calculus

Recall that the average velocity between times t1and t2 is calculated using vave = y(t2) − y(t1)/t2 − t1. We are given that y = 14t − 1.86t^2. Evaluating at t = 1, we have y(1) = 14(1) − 1.86(1)2 = 12.14. Thus, …
2. ### calculus

Let f(x) be the function 1/x+5. Then the quotient f(6+h)−f(6)/h can be simplified to −1/ah+b for: a= 11 b= I did all the work to get a but for some reason the number that I keep getting for "B" is wrong
3. ### MAth

Find f(a), f(a + h), and the difference quotient f(a + h) − f(a) ------------------ h , where h ≠ 0. f(x) = 2/x+5 f(a)= f(a + h) = f(a + h) − f(a) ----------------- = h
4. ### math

Find f(a), f(a + h), and the difference quotient f(a + h) − f(a) ------------------ h , where h ≠ 0. f(x) = x/x+6 f(a)= f(a + h) = f(a + h) − f(a) ----------------- = h
5. ### math

Find f(a), f(a + h), and the difference quotient f(a + h) − f(a) ------------------ h , where h ≠ 0. f(x) = 2x/x-7 f(a)= f(a + h) = f(a + h) − f(a) ----------------- = h
6. ### Math

Find f(a), f(a + h), and the difference quotient f(a + h) − f(a) ------------------ h , where h ≠ 0. f(x) = 4 − 6x + 7x2 f(a)= f(a + h) = f(a + h) − f(a) ----------------- = h
7. ### Math

Find f(a), f(a + h), and the difference quotient f(a + h) − f(a) ------------------ h , where h ≠ 0. f(x) = 7x^3 f(a)= f(a + h) = f(a + h) − f(a) ----------------- = h
8. ### Math

Simplify the difference quotient [f(2 + h) − f(2)]/h if h ≠ 0. f(x) = x^2 − 3x I keep getting the answer wrong...please help.
9. ### Mathematics

Simplify the difference quotient [f(x) − f(a]/[x − a] if x ≠ a. f(x) = SQROOT of (x − 27) (Hint: Rationalize the numerator.)
10. ### Pre-Calc

Simplify the difference quotient [f(2 + h) − f(2)]/h ; if h ≠ 0. f(x) = x2 − 3x I keep getting the answer wrong. I must be messing up my steps...Please Help

More Similar Questions